2002
DOI: 10.1051/0004-6361:20020630
|View full text |Cite
|
Sign up to set email alerts
|

Detection of HD in emission towards Sagittarius B2

Abstract: Abstract. The giant molecular cloud Sagittarius B2, located near the Galactic Centre, has been observed in the far-infrared by the ISO Long Wavelength Spectrometer. Wavelengths in the range 47-196 µm were covered with the high resolution Fabry-Pérot spectrometer, giving a spectral resolution of 30-40 km s −1 . The J = 1 → 0 and J = 2 → 1 rotational transitions of HD fall within this range at 112 µm and 56 µm. A probable detection was made of the ground state J = 1 → 0 line in emission but the J = 2 → 1 line wa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 23 publications
1
34
0
Order By: Relevance
“…In particular, we modelled the (Moos et al 2002 -at 3σ), along seven lines of sight. The three data points in the Galactic center are from Polehampton et al (2002), Lubowich et al (2000) and Jacq et al (1999). Lower panel: the seven lines of sight from FUSE mission observations, Moos et al (2002) and data, at 3σ, from other lines of sight observed by Copernicus, IMAPS, IUE and HST are shown.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, we modelled the (Moos et al 2002 -at 3σ), along seven lines of sight. The three data points in the Galactic center are from Polehampton et al (2002), Lubowich et al (2000) and Jacq et al (1999). Lower panel: the seven lines of sight from FUSE mission observations, Moos et al (2002) and data, at 3σ, from other lines of sight observed by Copernicus, IMAPS, IUE and HST are shown.…”
Section: Discussionmentioning
confidence: 99%
“…In the Galactic center region the D/H ratio is an order of magnitude less, as first estimated at mm. wavelengths from deuterated molecules by Jacq et al (1999), confirmed from radio observations of HCN and DCN by Lubowich et al (2000), and from ISO-FIR ratios of HD/H 2 by Polehampton et al (2002). Both the local and the Galactic center D abundances imply continuing infall to the Galaxy of gas which has suffered little previous net astration, the difference between them being due to the much more rapid destruction rate of D by astration in the Galactic centre.…”
Section: Introductionmentioning
confidence: 86%
“…The three observations were processed using the LWS pipeline version 8 and interactively calibrated using routines that appeared as part of the LWS Interactive Analysis (LIA) package version 10. The dark signal, including straylight, was determined as described in Polehampton et al (2002).…”
Section: Observations and Data Reductionmentioning
confidence: 99%
“…The remaining uncertainty in wavelength is less than 0.004 µm (or 11 km s −1 ), corresponding to the error in absolute wavelength calibration (see Gry et al 2002). A more detailed description of the calibration and reduction method is given in Polehampton (2002).…”
Section: Observations and Data Reductionmentioning
confidence: 99%
See 1 more Smart Citation